O-Phenyl (tert-butylamido)(p-tolylamido)phosphinate - Mehrdad Pourayoubi; Arnold L. Rheingold; Chao Chen; Fatemeh Karimi Ahmadabad; Atekeh Tarahhomi (Acta Crystallographica Section E, 2011)
In the title molecule, C17H23N2O2P, the P atom has a distorted tetrahedral environment. The P—N bond to the tolylamido fragment is 1.642 (4) Å while that to the butylamido fragment is 1.629 (3) Å. The dihedral angle between the two benzene rings is 82.3 (2)°. In the crystal, adjacent molecules are linked via weak N—H...(O)P and N—H...N hydrogen-bonding interactions into an extended chain parallel to the b axis. The three methyl groups of the tert-butylamido substituent are disordered over two sets of sites with equal occupancies. The crystal studied was found to be a non-merohedral twin with the minor twin component = 23.1 (1)%.